A numerical study on the effect of phase-change material (PCM) parameters on the thermal performance of lightweight building walls. (December 2021) - Liu, Zu'an; Hou, Jiawen; Meng, Xi; Dewancker, Bart Julien
Abstract: In recent years, lightweight buildings have been widely developed due to their sustainability advantages. However, lightweight buildings usually have sizeable indoor temperature fluctuations due to lower thermal mass. Phase change materials (PCM) have the characteristics of small temperature change and high energy storage density. Integrating PCM into lightweight building walls (LBW) can effectively enhance its thermal inertia and improve indoor thermal comfort. There are many discussions on building energy saving using PCM in the existing studies, but the research on the influence of PCM parameters on the thermal performance of LBW is insufficient. Therefore, a heat transfer model of LBW integrated with PCM was built and validated in this paper. The influence rules of different PCM parameters (transition temperature, location, thickness, latent heat, thermal conductivity, density, specific heat) on the thermal performance of LBW was analyzed and evaluated comprehensively by numerical simulation. The results show that: (1) PCM can significantly improve the thermal performance of LBW; (2) Each parameter of PCM has a relative optimal value; (3) PCM installed in the middle of the wall is better than the outside or inside at a suitable phase-transition temperature; (4) Under suitable PCM parameters compared with the reference wall (no PCM), the delay time ( φ ) is added to 6.86 h, the attenuation rate ( f ) decreases by 90.45%, the peak heat flux ( q peak ) and average heat flux ( q ave ) is reduced by 66.52% and 33.39%. The research results can provide reference and data support for the use of PCM in lightweight buildings.